Student Perception of the Application of Active Methodologies in a Computer-Aided Design Course - Chung-Pinzás, Alfonso Ramón; Inche-Mitma, Jorge Luís; Cruz-Chuquizuta, Consuelo (Revista Electrónica Educare, 2024)
Aim. This study aims to determine the impact of applying active methodologies (flipped classroom teaching, collaborative, and discovery learning) on students’ perception of the development of a computer-aided design (CAD) course. Method. The research employed a mixed-method design (quantitative - qualitative). For the stimulus, a teaching-learning environment was prepared and applied based on the aforementioned methodologies. Subsequently, data was collected from a sample of 132 industrial engineering students, using a five-level Likert scale questionnaire, previously validated and complemented with interviews from delegates of three sections. Quantitative data were analyzed using descriptive statistics and the sign test for inferential contrast, while qualitative data were examined through in-depth interviews with the delegates. Results. The students responded favorably to the applied methodologies. Likewise, methodologies encouraging students’ participation, making them the central actors and, at the same time, enabling them to construct their own paths to knowledge, were well received by students. Conclusions. The results showed a positive impact of the chosen active methodologies on student’s perceptions of the CAD course development. This research can be replicated in other CAD-related courses to gain a better understanding of the impact of those methodologies on students.